2021
DOI: 10.1364/oe.409879
|View full text |Cite
|
Sign up to set email alerts
|

High-power vacuum terahertz photomixer and integrated circuits based on microscale phototubes

Abstract: Technologies and industrials in long-distance communication, detection, and imaging applications are still in great need of higher-output-power terahertz sources. This paper proposes two kinds of microscale vacuum phototube based high-power terahertz source: vacuum photomixer and terahertz integrated circuit. The principle of photomixer based on photoemission and field-assisted photoemission is demonstrated. Its capability of producing radiation power beyond 1 mW is estimated based on theoretical analysis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Alternatively, high impedance photomixers can be used to significantly simplify the matching process. Nevertheless, this further diminishes the total antenna efficiency as THz photomixers still suffer from low conversion efficiencies and low output powers [24,159].…”
Section: Thz Resonant Antennasmentioning
confidence: 99%
“…Alternatively, high impedance photomixers can be used to significantly simplify the matching process. Nevertheless, this further diminishes the total antenna efficiency as THz photomixers still suffer from low conversion efficiencies and low output powers [24,159].…”
Section: Thz Resonant Antennasmentioning
confidence: 99%
“…[3,4] According to reports, the cutoff frequency of traditional photomixers has spanned multiple THz. [5,6] Only when a THz integrated antenna is in the diffusion region of a GaAs or InP PN junction, the minority of THz oscillation photocurrent generated by the PN junction [7,8] can be captured by an optical heterodyne down-conversion of two line-laser sources. Then, it will radiate forward space as a THz wave.…”
Section: Electron Beam Pumping Improves the Conversion Efficiency Of ...mentioning
confidence: 99%
“…The photon energy of terahertz waves is much smaller than that of X-rays, and this energy can be utilized to realize imaging detection for biosafety applications in the future. Because of this unique property, the development of terahertz light sources has become a research hot spot. It has been reported that InP-based resonant tunneling diode (RTD) terahertz devices can generate THz radiation when used as oscillators. However, owing to the narrow energy band of the material itself, the speed of saturation drift, and the effective quality of the electron, the low output power has become a major limitation for its development. GaN-based RTDs have been preferred for high output power terahertz oscillators owing to their large band gap, high thermal conductivity, and fast electron saturation drift. , However, after years of research, GaN-based RTD terahertz light sources have still not been realized.…”
Section: Introductionmentioning
confidence: 99%